On the phase diagram of the zero-bandwidth extended Hubbard model with intersite magnetic interactions for strong on-site repulsion limit - Murawski, Szymon; Kapcia, Konrad; Pawłowski, Grzegorz; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, Pl-02-668 Warsaw, Poland, 2012)
In this report we have analyzed a simple effective model for a description of magnetically ordered insulators. The Hamiltonian considered consists of the effective on-site interaction (U) and the intersite Ising-like magnetic exchange interaction (J) between nearest neighbors. For the first time the phase diagrams of this model have been determined within Monte Carlo simulation on 2D-square lattice. They have been compared with results obtained within variational approach, which treats the on-site term exactly and the intersite interactions within mean-field approximation. We show within both approaches that, depending on the values of interaction parameters and the electron concentration, the system can exhibit not only homogeneous phases: (anti-)ferromagnetic (F) and nonordered (NO), but also phase separated states (PS: F-NO).
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A. The Version of Record is available online at http://przyrbwn.icm.edu.pl/APP/PDF/121/a121z5p13.pdf
Keywords: magnetic orderings; phase separations; extended Hubbard model; atomic limit; Monte Carlo simulations